2017
DOI: 10.1007/s00784-017-2262-4
|View full text |Cite
|
Sign up to set email alerts
|

Dental implant surfaces after insertion in bone: an in vitro study in four commercial implant systems

Abstract: The given information is of value for daily implantation practice and the course of osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
1
22
1
Order By: Relevance
“…29,30 Only a few researchers held the perception that anodized implant surface modification may result in relatively severe alterations. 31 The previous studies did not reach an agreement on which kind of surface treatment was better; however, the SLA was deemed to be more reliable for short implants in this study. We hypothesized that the issue may be correlated with the time of osseointegration according to the result of survival analysis, which still requires experimental research.…”
Section: Discussioncontrasting
confidence: 47%
“…29,30 Only a few researchers held the perception that anodized implant surface modification may result in relatively severe alterations. 31 The previous studies did not reach an agreement on which kind of surface treatment was better; however, the SLA was deemed to be more reliable for short implants in this study. We hypothesized that the issue may be correlated with the time of osseointegration according to the result of survival analysis, which still requires experimental research.…”
Section: Discussioncontrasting
confidence: 47%
“…When the implant surface is treated by any of the methods exposed above, traces of the materials used, such as metals, metal ions, lubricants, and detergents, may appear. These elements can modify surface properties even when present in small quantities and may affect the body´s response during the osseointegration process, leading to the formation of undesirable tissues between bone/implant interface [18,19]. Although the effects caused by these low concentration trace elements are relatively weak studied, there is a broad agreement that comprehensive control of the implant surface and elimination of undesirable chemical compounds must be done to improve implant quality [20].…”
Section: Introductionmentioning
confidence: 99%
“…• An in vitro study showed that the insertion of oral implants could provoke the release of particles by stripping them off the surface (Deppe et al, 2017). Three implant systems with different surface roughness were placed in porcine bone of Class I according to Misch classification (Misch, 1999).…”
Section: Mechanical Wearmentioning
confidence: 99%